HUBUNGAN DUKUNGAN KELUARGA DENGAN PENERIMAAN DIRI PADA RESIDEN REHABILITASI DI LRPPN BHAYANGKARA INDONESIA MEDAN - Ningsih, Siska Dwi; Mora, Indo; Ramadhani, Sri; Tarihoran, Mia Solistika (Psikologi Universitas Sari Mutiara Indonesia, 2022)
After receiving the status of being a resident and undergoing the rehabilitation process, the negative stigma they received from the community had an impact on their self-assessment. During the pandemic, which limits the scope of socialization and activities as well as government programs for lock down, of course it will limit the number of visits by family members, reducing resident interactions with people from outside rehabilitation. Research This research on